THE ROLE OF TEACHERS IN ENHANCING READING INTEREST AMONG ELEMENTARY SCHOOL STUDENTS : A QUALITATIVE STUDY AT SD PLUS AL-ISHLAH BONDOWOSO - Achmad Bagus Sugiarto (Tsaqofah : Jurnal Pendidikan Islam, 2024)
This study aims to describe the role of teachers in fostering reading interest among fourth-grade students at SD Plus Al-Ishlah Bondowoso. The background of this research is the low level of student interest in reading, which negatively affects their comprehension skills and engagement in literacy activities. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The findings reveal that students' reading interest remains low, indicated by a lack of motivation to read outside of school assignments and a tendency to choose other activities during their free time. To address this issue, teachers played three essential roles: motivators, facilitators, and guides. They created a pleasant learning atmosphere, provided age-appropriate reading materials, and offered direct assistance throughout the reading process. Strategies implemented included shared reading, post-reading discussions, and reward-based systems. However, several obstacles hindered these efforts, such as limited instructional time, insufficient teacher training in literacy, and minimal parental involvement. This study underscores the significant role teachers play in cultivating a culture of literacy at the elementary school level and highlights the need for systemic support from both schools and families to sustainably enhance students’ reading interest.